Analisis Faktor-Faktor yang Memengaruhi Niat Mahasiswa Akuntansi dalam Mengikuti Sertifikasi Brevet Pajak di Semarang - Santoso, Andre Teguh; Nugraheni, Bernadia Linggar Yekti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the influence of self efficacy, grit personality, third party influence, attitude, prestige, and awareness on accounting students’ intention to obtain tax brevet certification. This quantitative research employed purposive quota sampling with 378 respondents from six accredited universities in Semarang. Data were collected through questionnaires and analyzed using SPSS to test validity, reliability, classical assumptions, and hypotheses. The results show that self-efficacy, third-party influence, attitude, prestige, and awareness have a significant positive effect on students’ intention, while grit personality has a significant negative effect. The negative grit effect indicates that high perseverance may reduce interest due to preference for broader long-term goals over immediate certification. Awareness is the strongest predictor, suggesting students who understand the career benefits are more motivated. External social influences and perceived prestige also enhance the intention to certify. The findings reinforce the Theory of Planned Behaviour by highlighting awareness as a key perceived behavioral control factor. Practically, universities should strengthen awareness programs and positive attitudes toward tac brevet certification. This study reveals the unique negative but significant effect of grit personality on certification intention, contrasting with most prior studies.